Epidemiological models - Μακρόγλου, Α.; Κουιμτζής, Σ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In this paper are described some epidemiological models which govern the spread of infectius diseases. These models are deterministic, and have the form of integral and integrodifferential equations. Solving these equations it is possible to predict the inumber of the confected members of a population at time t>0 if it Is known at time t=0.